1988
DOI: 10.1007/bf00377264
|View full text |Cite
|
Sign up to set email alerts
|

Plankton time ? space dynamics in German Bight ? a systems approach

Abstract: Long term continuous plankton measurements at Helgoland (North Sea) have provided a set of data which could be used for ecological functional analysis with respect to prey predator theory. Local dynamics display trophic feedback between selected populations. Phytoplankton, small copepods, Noctiluca miliaris, Pleurobrachia pileus and Beroe gracilis conform with theoretical assumptions. The functional relationships are less significant in averaged population dynamics compared with single ear processes. The local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The biomass of B. cucumis increased in Malangen in July, and its abundance peaked after that of B, infundibulum. This typical time lag between Beroe and its prey also has been described by Greve & Reiners (1988).…”
Section: Seasonal Variations Of Ctenophoresmentioning
confidence: 93%
See 1 more Smart Citation
“…The biomass of B. cucumis increased in Malangen in July, and its abundance peaked after that of B, infundibulum. This typical time lag between Beroe and its prey also has been described by Greve & Reiners (1988).…”
Section: Seasonal Variations Of Ctenophoresmentioning
confidence: 93%
“…High feeding and growth rates combined with high fecundity enable ctenophores to react quickly to changes in the environment, and the annual biomass extremes often span several orders of magnitude. Ctenophores are considered to be important regulators of mesozooplankton in coastal marine waters (Kremer 1979, Greve & Reiners 1980, 1988. However.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the database for mesozooplankton is consistent, and earlier observations can be compared to later ones without bias. Many examples of changing phenology (Greve and Reiners 1988;Greve et al 2005; have shown strong correlations between the sea surface temperature and the occurrence of several species, with higher temperatures usually leading to an earlier occurrence of the zooplankton species. Furthermore, several changes in the species composition have been noted, most conspicuously the increased abundance of the cladoceran Penilia avirostris (Johns et al 2005), the changing species composition within the genus Calanus (Helaouet and Beaugrand 2007) and the invasion of the ctenophore M. leidyi (Boersma et al 2007).…”
Section: Zooplanktonmentioning
confidence: 99%
“…Nevertheless, most populations of P. pileus show distinct seasonal fluctuations with, in the southern North Sea, individuals generally found between April and August (Greve and Reiners 1988). In recent years there seems to have been a shift in population dynamics, from a single very high peak in densities in May-June (Greve 1971) to a more even distribution over the whole summer (W. Greve, unpublished data), the causes of which are unknown.…”
Section: Introductionmentioning
confidence: 99%